Category and Syntactic Functions in the Collocation of the Words Wabah and Pandemic: A Corpus Linguistics Overview - Aditya Rachman; Rizaldy Hanifa; Ayu Gustia Ningsih; Selfi Mahat Putri; Ridha Hasnul Ulya (AL-ISHLAH: Jurnal Pendidikan, 2024)
The COVID-19 pandemic has transformed many aspects of life, including language. Words such as 'outbreak' and 'pandemic' frequently appear in COVID-19-related news, and both carry similar meanings in referring to the rapid spread of contagious diseases that affect a large number of people in extensive areas. Although these terms are often used interchangeably, it remains unclear how they are employed in various sentence contexts. This research aims to analyze the categories and syntactic functions of the collocation of the words 'outbreak' and 'pandemic' in the Nusantara Corpus using a corpus linguistics method. The study utilizes a combined quantitative and qualitative approach to examine the collocation of 'outbreak' and 'pandemic' in the Nusantara Linguistic Corpus. Data analysis is based on corpus linguistic theory and collocation theory. The research findings indicate that the collocation of 'outbreak' and 'pandemic' words is identified in the Nusantara corpus. The frequency of the word 'outbreak' reaches 195 occurrences, while 'pandemic' appears 1,229 times. Therefore, it can be concluded that the collocation of 'outbreak' and 'pandemic' words can be syntactically categorized as verbs, nouns, adjectives, and prepositions. Moreover, in terms of syntactic functions, the collocation of 'outbreak' and 'pandemic' is classified as subjects, objects, complements, and adverbials. This research can be implemented in the use of 'outbreak' and 'pandemic' collocations in sentence construction by considering categories and syntactic functions to avoid semantic errors based on the correct context.